Levofloxacin or Clarithromycin-based quadruple regimens: what is the best alternative as first-line treatment for Helicobacter pylori eradication in a country with high resistance rates for both antibiotics?. Issue 1 (December 2017) - Branquinho, Diogo; Almeida, Nuno; Gregório, Carlos; Cabral, José; Casela, Adriano; Donato, Maria; Tomé, Luís
Abstract Background Helicobacter pylori eradication rates in Portugal are declining, due to increased resistance of this bacterium to antimicrobial agents, especially Clarithromycin. Quadruple Levofloxacin-containing regimens could be an option for first-line treatment, but its efficacy should be evaluated as fluoroquinolone resistance is rapidly increasing. Our aim was to compare the efficacy of Clarithromycin and Levofloxacin-based sequential quadruple therapies as first-line treatment options and determine factors associated with treatment failure. Methods A total of 200Helicobacter pylori infected patients were retrospectively included (female 57.5%; average age: 53.2 ± 15.7) and received either 10-day sequential therapy (Proton-Pump Inhibitor + Amoxicillin 1 g bid for 5 days and Proton-Pump Inhibitor + Clarithromycin 500 mg + Metronidazole/Tinidazole 500 mg bid/tid in the following 5 days; group A) or a 10-day modified sequential therapy with Levofloxacin 500 mg id instead of Clarithromycin (group B). Eradication was confirmed with urea breath test. Variables that could influence success rate were analyzed. Results There were no differences between groups in terms of gender, age, smoking habits and indications for treatment. The eradication rate obtained with Clarithromycin-based sequential treatment was significantly higher than with Levofloxacin-based therapy (90%, CI95%: 84–96% vs. 79%, CI95%: 71–87%, p  = 0.001). Using full-dose proton-pump inhibitor and high-dose Metronidazole in group A, and full-dose proton-pump inhibitor and prescription from a Gastroenterologist in group B were associated with eradication success. Conclusions Ten-day Levofloxacin-based sequential treatment achieved inadequate efficacy rate (<80%) and should not be adopted as first-line therapy. Standard sequential therapy showed significantly better results in thisnaïve population. Using full-dose proton-pump inhibitor and higher doses of Metronidazole is essential to achieve such results.